Age-related clinical and hemodynamic outcome following transcatheter aortic valve replacement: a swiss TAVI registry analysis. (25th November 2020) - Attinger, A; Ferrari, E; Muller, O; Nietlispach, F; Toggweiler, S; Maisano, F; Roffi, M; Jeger, R; Huber, C; Carrel, T; Windecker, S; Togni, M; et al.
Abstract: Background: Transcatheter aortic valve implantation (TA) is the preferred treatment modality for patients with severe aortic valve disease at high surgical risk and is expanding into lower risk populations. Therefore age range of treated patients is increasing. Purpose: The aim of this study is to analyze age-related clinical and hemodynamic outcome of patients following TAVI in a nationwide, prospective, multicentre cohort (Swiss TAVI registry). Methods: We retrospectively analyzed prospectively collected data from all patients included in the Swiss TAVI registry between February 2011 and December 2018. In an adjusted analysis, in-hospital, 30-days and 1-year outcome between four age groups were compared. Results: Overall, 7097 patients underwent TAVI (<70 years: n=324, 70–79 years: n=1913, 80–89 years: n=4353, 90–100 years n=507). Median STS risk score for mortality was 5.23±4.13% and differed significantly between age groups (3.46±4.10%, 3.97±3.73%, 5.57±3.97%, 8.22±4.74%; p=0.001). Valve predilatation was more often performed in older patients (54.3% vs. 54.3% vs. 60.7% vs. 69.6%; p≤0.001). Difference in hospital stay was statistically sigificant between age groups, numerically however not relevant (10.01±7.56 days vs. 9.25±6.38 days vs. 9.55±5.70 days vs 10.03±5.77 days; p=0.02). Post-procedural acute kidney injury stage 3 was highest in the youngest age group (3.4% vs. 1.6% vs. 1.1% vs. 1.0%; RR [95% CI] 0.65 (0.48–0.87); p=0, 004) and rate of new pacemakers for conduction abnormalities increased significantly with age (10.2% vs. 13.7% vs. 17.1% vs. 18.7%; RR [95% CI] 1.22 (1.12–1.32); p<0.001). There was no significant difference in life threatening/major bleeding (p=0.288/0.197) or major vascular complications (p=0.083). All-cause mortality and cardiovascular mortality in hospital, at 30 days and at 1 year were highest in nonagenarians and higher in the patients <70 years compared to patients of 70–79 years: in hospital all-cause mortality 2.2% vs. 1.6% vs. 2.9% vs. 5.5% (RR [95% CI] 1.64 (1.28–2.10), p<0.001); 30 day all-cause mortality 3.1% vs. 2.0% vs. 3.7% vs. 6.7%; (HR [95% CI] 1.59 (1.30–1.96); p<0.0001); 1-year all-cause mortality 10.9% vs. 10.4% vs. 12% vs. 19.5% (HR [95% CI] 1.27 (1.14–1.41); p<0.001); in hospital cardiovascular mortality 1.5% vs. 1.5% vs. 2.6% vs. 5.1% (RR [95% CI] 1.70 (1.31–2.20), p<0.001); 30 day cardiovascular mortality 2.2% vs. 1.9% vs. 3.3% vs. 6.3%; (HR [95% CI] 1.68 (1.35–2.09); p<0.001); 1-year cardiovascular mortality 7.2% vs. 6.9% vs. 8.3% vs. 15.3% (HR [95% CI] 1.36 (1.19–1.55); p<0.001). This held true, when hazard ratio was corrected for STS PROM score, femoral access vs other access and year of procedure. Conclusion: In-hospital, 30-day and 1-year clinical outcome of nonagenarians undergoing TAVI are less favorable compared to lower age groups. Interestingly, clinical outcome of the patients group 70–79 years was the most favorable. Funding Acknowledgement: Type of funding source: None